2006
DOI: 10.1097/01.ftd.0000249947.17676.92
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thiopurine S-methyltransferase Polymorphism in the Population of Serbia and Montenegro and Mercaptopurine Therapy Tolerance in Childhood Acute Lymphoblastic Leukemia

Abstract: Thiopurine S-methyltransferase (TPMT) is an enzyme that converts thiopurine drugs into inactive metabolites. It is now well established that interindividual variation in sensitivity to thiopurines can be the result of the presence of genetic polymorphisms in the TPMT gene. The aim of this study was to determine the frequency and type of TPMT polymorphisms in the population of Serbia and Montenegro and to assess its relevance in the management of childhood acute lymphoblastic leukemia (ALL). Blood samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 53 publications
4
31
0
4
Order By: Relevance
“…The results for the Croatian and Slovenian samples do not differ for TPMT*2 variant allele, as the Real-time PCR was applied on both sides, but differ for other alleles where the methods were different 12 . Our data are in accordance with the data obtained for Serbian population 14 . Since our laboratory is taking part in the external quality control schemes (DGKL, Germany) for TPMT genotyping, we are rather confident for the data presented in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results for the Croatian and Slovenian samples do not differ for TPMT*2 variant allele, as the Real-time PCR was applied on both sides, but differ for other alleles where the methods were different 12 . Our data are in accordance with the data obtained for Serbian population 14 . Since our laboratory is taking part in the external quality control schemes (DGKL, Germany) for TPMT genotyping, we are rather confident for the data presented in this study.…”
Section: Discussionsupporting
confidence: 82%
“…A few reports on Slavic populations have revealed differences in the frequency of variant alleles among Slavic populations [10][11][12][13][14][15] . This is the first study on TPMT polymorphisms in a Croatian population of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that genetic TPMT variants in exons account for 7.5% of all TPMT variants with decreased enzyme activity (11). Similar to the other Caucasian subjects, TPMT*3A is the most prevalent variant allele in Serbia (3.2%).…”
Section: Tpmt Gene Polymorphisms Is Serbiasupporting
confidence: 49%
“…Consequently, thiopurine drug dose reduction is necessary to avoid toxicity (8). Patients with intermediate TPMT activity also require dose reduction (8,11). Therefore, knowledge of the level of TPMT enzyme activity is essential for the balance of therapeutic and toxic effects of thiopurine drug dose.…”
Section: Tpmt Allozymesmentioning
confidence: 99%
“…Additionally, prior to application of irinotecan therapy, used for colorectal and pulmonary cancer treatment, pharmacogenomic markers in the UGT1A1 (uridine diphosphate glucuronosyltransferase 1 family, polypeptide A1) gene need to be analyzed (46). Variants in the TPMT gene (thiopurine S-methyltransferase) are tested in order to adjust immunosuppressive therapy (6-mercaptopurine, azathioprine and thioguanine), used in the treatment of acute leukemia, inflammatory and autoimmune diseases and in transplantation medicine (47,48).…”
Section: Pharmacogenetics and Pharmacogenomicsmentioning
confidence: 99%